Construction of Binary Vector With Wound Inducible Promoter for Hbsag Expression: Development of Plant-Based Edible Hepatitis B Vaccine from Indonesian Isolate - Sony Suhandono; Ernawati A.Giri Rachman; Ima M. Zainuddin; Putri Dwi Utari; Apsari Supraba; Amy Estiati (ANNALES BOGORIENSES, 2007)
Hepatitis B is a serious infectious disease In the third world countries including Indonesia . Vaccination is  the most effective way to prevent the spread of the disease;  therefore the demand for HBV vaccine is high.  In order to produce more vaccine at lower cost, transgenic plant can be chosen to express the vaccine with the above criteria. Several researches were successfully producing transgenic plants expressing HBsAg that formed virus-like particles and  induced  immune response  in  human.  However. HBsAg expression  in  transgenic plant needs to be  improved especially on gene  expression control system. Here, we describe the construction of HBsAg .  structural gene under the control of wound  inducible promoter, MeEFl promoter from  manihot esculenta Crantz. The HBsAg gene was amplified using PCR from HBV genome isolated from an  Indonesian patient. The gene was subsequently fused with VSPaS signal peptide, which targeted the reticulum endoplasm of plant cell . The construct was cloned into binary expression vector for Agrobacterium plant Transformation  in  near future.Keywords: HBsAg. VSPaS signal peptide and MeEFI promoter